Biomechanical Evaluation of 3 Stabilization Methods on Acromioclavicular Joint Dislocations. (June 2013) - Nüchtern, Jakob V.; Sellenschloh, Kay; Bishop, Nick; Jauch, Sabrina; Briem, Daniel; Hoffmann, Michael; Lehmann, Wolfgang; Pueschel, Klaus; Morlock, Michael M.; Rueger, Johannes M.; Großterlinden, Lars G.
Background: Traumatic acromioclavicular (AC) joint dislocations can be addressed with several surgical stabilization techniques. The aim of this in vitro study was to evaluate biomechanical features of the native joint compared with 3 different stabilization methods: locking hook plate (HP), TightRope (TR), and bone anchor system (AS). Hypothesis: The HP provides higher stiffness than the anatomic reconstruction techniques. Study Design: Controlled laboratory study. Methods: A new biomechanical in vitro model of the AC joint was used to analyze joint stability after surgical repair (HP, TR, and AS). Eighteen cadaveric specimens were randomized for bone density and diameter in the midclavicle section. Joint stiffness was measured by applying an axial load and a defined physiological range of motion for internal and external rotations and upward and downward rotations. Data were recorded at 3 stages: for the native joint after dissecting the AC ligaments, directly after repair, and after axial cyclic loading (1000 cycles with 20 and 70 N at 1 Hz). To evaluate which implant mimics physiological joint properties best, axial stiffness of vertical stability was assessed in combination with rotation. Finally, static loading in the superior direction was applied until failure of the joints occurred. Results: Axial stiffness of the TR and AS groups was 2-fold higher than for the HP group and the native joint (67.1, 66.1, and 22.5 N/mm, respectively; P < .004). Decreased load-to-failure rates were recorded in the HP group compared with the TR and AS groups (248.9 ± 72.7, 832.0 ± 401.4, and 538.0 ± 166.1 N, respectively). The stiffness of the rotations was not significantly different between the treatment methods but was lower in horizontal and downward rotations compared with the native state. Thus, native AC ligaments contributed a significant share to joint stiffness. Conclusion: The TR and AS groups demonstrated higher vertical load capacity. Compared with the TR and AS, the HP demonstrated an axial stiffness closest to the native joint. For restoring physiological properties, reconstruction of the AC ligaments may be necessary. Clinical Relevance: The results show different biomechanical properties of the HP and anatomic reconstructions.